Development of a Bacteriophage Cocktail to Evaluate In Vitro and In Vivo Therapeutic Efficacy Against ESBL Producing Klebsiella pneumoniae - Sidrah Asghar; Ayaz Ahmed (Journal of Global Antimicrobial Resistance)
INTRODUCTION: Klebsiella pneumoniae as commensal Gram-negative bacilli and a member of ESKAPE pathogens is common cause of bacteremia, endocarditis, wound, respiratory and urinary tract infections. Since the arrival of antibiotic therapy, there has been a parallel increase in the evolution of antimicrobial resistant pathogens. Emerging antibiotic resistance, demands an alternate option to cure multidrug-resistant K. pneumoniae infection. The use of bacteriophages in the pre-antibiotic era and recent development in phage therapy highlight them as a potential alternate to cure K. pneumoniae specific infections. METHODOLOGY: From environmental samples, phage isolation was done. Phages were characterized phenotypically and genotypically. Purified phages were combined to develop a phage cocktail which comprised of two distinct phages. Phage cocktail efficacy on planktonic and mature biofilm was determined via different microscopic techniques. Later, the hypothesis to formulate a phage-based therapeutic cocktail was evaluated in in vivo bacteremia models using K. pneumoniae as model organism. RESULTS: Two phage A¥L and A¥M were selected, based on its severe lytic action and had a significant impact on K. pneumoniae biofilm formation. Both phages have specificity towards K. pneumoniae and incredible phage tolerability at different pH and temperatures. A¥L phage belongs to the myoviridae family and A¥M belongs to siphoviridae family. Moreover, phage cocktail showed significant biofilm eradication as visualized via AFM, SEM, and fluorescent and bright field microscopy. Later, in vivo study showed successive bacterial reduction and survival. CONCLUSION: These findings imply that the phage might be a good option for eliminating K. pneumoniae infections in clinical settings.